Multidimensional Space: The Intersection of Architecture and Engineering in the Realm of the Senses - Erwine, Barbara (ARCC Conference Repository, 2014)
The historically lush and varied sensory environments we evolved in have paled to a relatively bland homogeneous palette. With ever-increasing technological accuracy, the environments we now design and build are controlled to narrowly acceptable ranges of temperature, light, smell, sound and color. To address the comparatively impoverished sensory environments prevalent in contemporary architectural/urban design practice, this paper explores the intersection of the design and engineering professions as they overlap inthe realm of the senses. The paper presents a new framework for design of sensory spaces including light, color, temperature, smell, sound, touch and the personal and communal spaces brought to life through habitual use patterns. Each of these sensory dimensions is identified as an independently shaped space with attendant characteristics of location, boundary, intensity, duration, etc. which may coincide with or only partially overlap the architectural geometric space of solids and voids. The multidimensional design framework outlined in the paper explores how these sensory spaces may be either congruent, reinforcing each other for anintense nodal experience, or dissonant, diverging to create an illusion. To accomplish the paradigm shift required to implement the framework, the paper addresses the current silos of design and engineering professions and explores a collaborative relationship between them, where architects and urban planners move to embrace the traditional engineering realm of environmental controls and engineers claim their due place in the design arena.